TikTok Content Marketing and Live Shopping as Economic Drivers of Consumer Purchase Intention (Case of Artasedana Supermarket, Singaraja) - Yanti, Kadek Anggel Darma; Astana, I Gusti Made Oka (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the economic influence of TikTok-based content marketing and live shopping on consumer purchase intention for products at PT Artasedana Singaraja. In response to the rapid advancement of information technology and the widespread use of social media—particularly TikTok—businesses encounter both new opportunities and challenges in attracting and retaining consumers. TikTok’s e-commerce features have transformed the platform into an effective digital marketing tool, enabling companies to promote products and engage directly with potential buyers. By implementing creative content marketing and interactive live shopping strategies, PT Artasedana strives to boost consumer purchase intention and improve its mkarket performance. This research employs a quantitative approach to measure the impact of these marketing techniques on consumer behavior. The findings are expected to offer practical insights for businesses in optimizing digital marketing efforts and enhancing economic outcomes in a highly competitive retail environment. Additionally, this study contributes to the growing body of marketing literature, particularly in the context of Indonesia's retail sector.